(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and histopathological characteristics of differentiated thyroid cancer at Military Hospital 175. Subjects and Methods: A descriptive cross-sectional study combined with a prospective design was conducted on 42 patients diagnosed with differentiated thyroid cancer at Military Hospital 175 from July 2022 to January 2024. Results: The mean age of patients was 45.8 ± 9.6 years, with a predominance of females (71.4%). Papillary carcinoma accounted for the majority of histopathological types (90.5%), with capsular invasion in 11.9% and invasion of adjacent organs in 4.8% of cases. The disease stages were predominantly T1 and T2 (64.3%), with no lymph node metastasis (76.2%) and no distant metastasis (97.6%). There were significant associations between age, gender, tumor size, and the status of lymph node metastasis and capsular invasion (p<0.05). Within one year post-surgery, the recurrence-free rate was 92.9%, with local recurrence at 4.7% and distant recurrence at 2.4%. Conclusion: Differentiated thyroid cancer has a favorable prognosis with a high one-year recurrence-free rate. However, risk factors such as tumor size and invasion status should be carefully considered in diagnosis and treatment.